1992
DOI: 10.1097/00000658-199204000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Serum Level During Severe Sepsis in Human IL-6 as a Marker of Severity

Abstract: Forty critically ill surgical patients with documented infections were studied during their stay in an intensive care unit. Among these patients, 19 developed septic shock and 16 died, 9 of them from septic shock. Interleukin 1 beta (IL-1 beta), tumor necrosis factor (TNF alpha), and interleukin 6 (IL-6) were measured each day and every 1 or 2 hours when septic shock occurred. Although IL-1 beta was never found, TNF alpha was most often observed in the serum at a level under 100 pg/mL except during septic shoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
390
4
15

Year Published

1994
1994
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 752 publications
(438 citation statements)
references
References 25 publications
29
390
4
15
Order By: Relevance
“…These findings suggest that one cannot ascertain whether IL-ip plays a role in the pathogenesis of septic myocardial depression in the clinical setting on the basis of serum IL-lp concentration alone. On the other hand, the concentrations of the other cytokines TNF-a and IL-6 have been shown to be related to the severity of sepsis and prognosis of the patients with sepsis and/or septic shock (14,15). This may reflect the pathophysiologic relation between these cytokines and "septic myocardial depression" previously shown in many experimental studies (6-10, ll).…”
Section: Discussionmentioning
confidence: 88%
“…These findings suggest that one cannot ascertain whether IL-ip plays a role in the pathogenesis of septic myocardial depression in the clinical setting on the basis of serum IL-lp concentration alone. On the other hand, the concentrations of the other cytokines TNF-a and IL-6 have been shown to be related to the severity of sepsis and prognosis of the patients with sepsis and/or septic shock (14,15). This may reflect the pathophysiologic relation between these cytokines and "septic myocardial depression" previously shown in many experimental studies (6-10, ll).…”
Section: Discussionmentioning
confidence: 88%
“…Since inflammatory cytokines are thought to be good markers of the severity of bacterial infections (8,20,30), we measured the levels of IL-1␤, IL-6, and TNF-␣ in the blood and liver tissues of the mice after the induction of gut-derived sepsis. Samples from each group of mice (n ϭ 9) were collected 2 days after the second administration of cyclophosphamide.…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, it has been shown that the increase in concentration of IL-6 correlates well with operating time, severity of sepsis, and clinical complications after surgery (Damas et al, 1992). However, little is known about the IL-2 changes in response to surgery.…”
Section: Modulation Of Cytokine Production By Tramadolmentioning
confidence: 99%